Studi Kritis Buku Ulumul Hadits Karya Ali Musthafa Ya'qub - Dadah Dadah; Saefuddin Nur; Siti Rahmah (Program Studi Ilmu Hadis STAIN Mandailing Natal, 2025)
This study aims to assess the effectiveness of using the Ensiklopedia Hadis 9 Imam application in supporting the digital-based takhrij hadith process. The increasing use of digital platforms in hadith studies requires critical evaluation of data accuracy, feature reliability, and relevance to research needs. This study uses a qualitative-descriptive method with data collection through literature study, direct observation of application features, and interviews with active users. The results show that this application can accelerate the process of searching for hadith, facilitate the identification of sanad and matn, and provide quick access to translations and basic information about narrators. However, a number of limitations were found, such as the lack of in-depth sanad analysis, dependence on manual verification using classical sources, and restrictions on certain features for non-premium users. This study concludes that the application is effective as an initial tool, but cannot replace the more comprehensive traditional takhrij methodology. Based on these findings, the study recommends that the use of digital applications always be followed by verification in the main books and scientific literature to maintain the validity and integrity of hadith studies.